PROGNOSTIC VALUE NT PRO-BNP IN PATIENTS WITH ACS - Kopytsya, M. P.; Tytarenko, N. V.; Bila, N. V.; Oparin, O. L. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The aim of this study was to define the utility of the measurement N-terminal pro-brain natriuretic peptide (NTproBNP) and other clinical and biochemical markers to predict adverse events at 1 year in patients with ACS. Parameters with significant differences in died and surviving patients were taken for analysis: age, heart rate (HR) at admission, levels of hemoglobin and NTproBNP. Curves of sensitivity and specificity were used based on the method of ROC analysis and cut-off values were chosen for each variable. Ball scoring was performed for each parameter regard to the cut-off value and a scale for calculating the summarized diagnostic coefficient (DC) by the method of Gubler was offered. A multimarker approach included on NTproBNP, hemoglobin, HR at admission and age and the summation of balls based on offered scale and calculating DC provides information in terms of ACS prognosis at 1 year, with a worse outcome for those with diagnostic coefficient has positive value (sensitivity 88,9 % and specificity 93,8 %).